Budesonide/formoterol for pediatric asthma: bridging the gap between evidence and practice in Maintenance and Reliever Therapy - Tian, Fu-xiang; Wang, Xiu-ping; Wang, Dong-mei (Frontiers in Medicine, 2025)
Budesonide/formoterol is established as a foundational therapy for moderate-to-severe pediatric asthma, with extensive evidence supporting its efficacy in both maintenance and Maintenance and Reliever Therapy regimens. Its dual pharmacologic profile provides distinct advantages in exacerbation reduction and symptom control. However, clinical implementation faces persistent challenges, including diagnostic uncertainty in young children, technical difficulties in device use, variable adherence, and perceptual barriers among clinicians and caregivers. Future advancement requires targeted research into phenotype-specific treatment responses, integration of digital health technologies for personalized management, and systematic reform in education and policy. A multidisciplinary effort is essential to achieve more precise, effective, and sustainable asthma control in the pediatric population.